Approximate Controllability of Second Order Neutral Stochastic Integro Differential Equations with Impulses Driven By Fractional Brownian Motion - Madhuri, S.; G.V.S.R., Deekshitulu (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper we introduce a class of second order neutral stochastic integro differential equations with impulses that are governed by fractional Brownian motion in Hilbert space. First, we establish the existence of mild solution using Banach fixed point theorem. Further approximate controllability for this system is formulated by assuming that the corresponding linear system is approximately controllable. The results are illustrated with example.